Information literacy abilities in ESL classrooms - Azwan Shaiza Nizam; Normazidah Che Musa; Wahiza Wahi (Penerbit Universiti Kebangsaan Malaysia, 2010)
Recent advancements in information and communication technologies have directly affected education, as it requires learners to be more information literate to achieve academic success. Information literacy (IL), defined as the “ability to access, evaluate and use information from a variety of sources” (ANZIIL Framework, 2004, p.3) is seen as a prerequisite for achieving learners’ purposes and goals. This article reports on a study of IL abilities of ten university students as they worked on their English Language class assignments. We evaluated these abilities through document analysis, a student questionnaire, and interviews with three teachers who taught these students. The results show the effect of students’ level of English Language proficiency on their IL abilities. These findings suggest the need for English Language classes to provide more opportunities and guidance for these learners to become more competent and independent information users